Revisionary narratives : Moroccan women's auto/biographical and testimonial acts - Hachad, Naïma (Contemporary French and francophone cultures, 2019)
Revisionary Narratives examines the historical and formal evolutions of Moroccan women's auto/biography and testimony. Considering works in Arabic, Moroccan Darija, French, and English in the fields of prison narratives, visual arts, theater, and digital media, the book highlights strategies women use to relate their experiences of political violence, migration, displacement, and globalization while also decentering patriarchal and (neo)imperial norms and practices.